The impact of the digital economy on sustainable development: evidence from China - An, Qiguang; Wang, Ruoyu; Wang, Yongkai; Pavel, Kolomiets (Frontiers in Environmental Science, 2024)
This research investigates the intricate interplay among the digital economy, green innovation, and the level of sustainable development. Panel data from 268 cities in China, from 2011 to 2020, are used to comprehensively evaluate the level of digital economy development and investigate the digital economy’s influence on sustainable development. Additionally, a mechanism analysis is used to investigate the contribution of green innovation. The findings suggest that the digital economy significantly stimulates sustainable development, and green innovation serves as a mediating intermediary and moderating effect in facilitating this relationship. Moreover, the robustness check extends the verification of the positive effect of the “Broadband China” policy on sustainable development, strengthening the reliability of the results. The contribution of this study provides management insights on how regions can promote sustainable development in the digital age.